Experiential contacts with green infrastructure’s diversity and well-being of urban community - Mansor, Mazlina; Said, Ismail; Mohamad, Ismail (Faculty of Architecture, Planning and Surveying, UiTM, 2010)
The study explores the significance of residents’ experience with an array of green infrastructure in Taiping, a small town in central Peninsular Malaysia. It argues that the existence of a composite of greenery and open spaces in a town that has diversity contributes to sense of well-being of residents. Green infrastructure network is a composite of various types of greenery and open spaces linked by streets, waterways and drainages encircling and connecting urban areas, at all spatial scales. In Taiping, the green infrastructure network consists of a town park, street planting, open spaces of public buildings, pocket spaces between shop-houses, school playfields, neighbourhood open space, home gardens, and river corridors. Questionnaires (n=335) and semi-structured interviews (n=33) explored the diversity of the green infrastructure in the town and the causal relationship to well-being—physical, cognitive and social. The data suggested that green infrastructure afford residents diversity of experience. Diverse experiences of green infrastructure network, physically and visually attract residents to participate in active activities, to socialize and to perform other transactional activities outside their homes. Therefore, the effects from the participation trigger many positive moods such as serenity, relaxation, comfort and satisfaction. Moreover, in physical and social terms, experiencing urban green spaces such as parks and gardens afford town residents active living, and community participation and harmony. There were modest relationships between the dimensions of diversity with the well-being dimensions, suggesting that residents felt diversity affect their sense of well-being. Hence, the results implicate that urban green spaces are essential amenity for towns and cities that afford an individual and a community physical, cognitive and social well-being.